Generating timely molecular diagnostic test results: workflow comparison of the cobas® 6800/8800 to Panther. (3rd October 2019) - Aretzweiler, Gudrun; Leuchter, Susanne; Simon, Christian O; Marins, Ed; Frontzek, Andre
ABSTRACT: Background : Molecular diagnostic tests for HBV, HCV and HIV-1 and other pathogens are widely used for clinical management. Practical issues related to workflow and labor requirements need to be characterized to inform selection of the most appropriate system. Research design and methods : We compared the workflow of two high-throughput systems: cobas 6800 (Roche) and Panther (Hologic), using average mid-size laboratory test volumes for five different assays (HIV-1, HBV, HCV, HPV or TV, and CT/NG). Results : Set-up time, time to first results, time to last results, and total hands-on time for cobas 6800 was 0.40, 2.47, 7.12, and 0.98 hours, respectively; on the Panther system, these times were 0.75, 2.7, 9.1, and 1.48 hours. Fifty-seven samples had results available at the first time point on cobas 6800 compared to 5 samples on the Panther system. The Panther system required more manual steps including several with potential risks of contamination or error. The number of reagents items required was 5 for cobas 6800 and 40 for the Panther system. Conclusions : Both systems provided a high level of automation. The cobas 6800 platform had shorter start up, time to first result, time to last result and hands-on times than the Panther system.